Improving Students’ Evaluation and Explanation Skills in Statistics using 9 E Teaching and Learning Model: an Experimental Study - Khalid Javed Assi; Norazlinda Saad; Surendran Sankaran (Universitas Riau, 2022)
The study was designed to compare the effectiveness of 9E teaching and learning model with Induction and Deduction Method (IDM). In this study the sample size of 124 students of Bachelor of Science (BS) 4 years (62 boys and 60 girls) was randomly selected. The experimental and control group design was used with pretest and posttest to observe the evaluation and explanation skill of the learners by Critical Thinking Skills (CTS). The selected students were divided into two groups i.e. experimental and control group. Experimental group was comprised of 62 students (31 boys and 30 girls) control group was consisted of 62 students (31 boys and 30 girls) teaching with IDM. The students were given treatment of 9E teaching and learning (elicit, engage, explore, explain, echo, elaborate, evaluate, emend and E-search) method. SPSS (V-23) data analysis was used in pretest and posttest for ANCOVA and independent sample t-test. It was observed that in posttest results of students (9ETLM). A significance difference was observed in the 9ETLM. The findings of the research indicate that the performance of the experimental group was better than the performance of the control group. However, there was some interaction between gender of EES and effect of conduct. It was strongly recommended to adopt and teach with 9 E teaching and learning model in different science and statistics subject during teaching in general and especially in statistics.